1995
DOI: 10.1176/ajp.152.9.1291
|View full text |Cite
|
Sign up to set email alerts
|

Increases in CSF levels of interleukin-2 in schizophrenia: effects of recurrence of psychosis and medication status

Abstract: Levels of interleukin-2, a molecule that plays both neurodevelopmental and neuroregulatory roles, may have a role in relapse in schizophrenia. Levels of CSF interleukin-2 appear to be affected by relapse mechanisms, while peripheral blood levels are not. These changes are specific to interleukin-2, since levels of interleukin-1 alpha were affected by medication withdrawal but not by change in clinical state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(21 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Polymorphisms of the IL-1 gene complex have been associated with schizophrenia (Xu and He, 2010) and, specifically, ventricular enlargement (Papiol et al, 2005). High levels of pro-inflammatory cytokines such as IL-1β, IL-6, and IL-2 have also been observed in the CSF of patients with schizophrenia, further supporting this effect (Garver et al, 2003; McAllister et al, 1995; Soderlund et al, 2009). …”
Section: Systemic Inflammation Neuroinflammation and Neuroprogrementioning
confidence: 76%
“…Polymorphisms of the IL-1 gene complex have been associated with schizophrenia (Xu and He, 2010) and, specifically, ventricular enlargement (Papiol et al, 2005). High levels of pro-inflammatory cytokines such as IL-1β, IL-6, and IL-2 have also been observed in the CSF of patients with schizophrenia, further supporting this effect (Garver et al, 2003; McAllister et al, 1995; Soderlund et al, 2009). …”
Section: Systemic Inflammation Neuroinflammation and Neuroprogrementioning
confidence: 76%
“…Thus, given the efficacy of adjunctive NSAIDs in improving psychopathology in relapsed patients (7-11), these findings support the plausibility of the hypothesis that immune changes are not a merely artifact of increased stress associated with acute psychosis, but may play a role in the pathophysiology of relapse in schizophrenia. In addition to the association between monocytosis and worsening psychosis mentioned above (28), other studies have found that intra-individual changes in other immune parameters, including CSF IL-2 levels and in vitro IL-2 production may predict relapse in some patients (77,78). Further investigation of potential relapse predictive markers is needed.…”
Section: Discussionmentioning
confidence: 92%
“…Within schizophrenia, in a study of 36 patients who underwent weekly assessments for 1 year, in vitro IL-2 production plus antihippocampal immunoglobulin G levels from the previous week significantly predicted relapse in three of seven patients (102). Similarly, in a study of 64 male subjects with schizophrenia, increased CSF IL-2 levels following haloper-idol withdrawal were a significant predictor of acute psychotic relapse (78). Our finding of significant alterations in cytokine (and cytokine receptor and antagonist) levels in acute illness exacerbations, measured within days of admission, that start to normalize following antipsychotic treatment support the plausibility of cytokine levels as a putative state-related marker for acute psychosis.…”
Section: Discussionmentioning
confidence: 98%